Socio-economics characteristics and spatial persistence of homicides in Colombia, 2000-2010 - Sandoval, Luis Eduardo (Estudios de Economía, 2018)
This paper studies the spatial effects of demographic changes, education conditions and conflict situation on the spatial persistence in the municipal homicide rate in Colombia, as a result of shock increases in the displaced population and local residents between 15-29 years old, the education coverage, and the conflict actions. In order to do this, a temporal analysis of homicides rate during 2000-2010 is undertaken through the inclusion of temporal dynamic characteristics in a spatial autoregressive model, a spatial weights matrix was constructed that was based on the distance travelled between near-by municipalities and the departmental capital cities which were defined as centroids, which standardizes the municipal relationship that affects the demographic dynamics and social connectivity of the last decade that affects homicides and their temporal persistence. The results show that in some departments of the country there is spatial agglomeration in homicide rates in nearby municipalities but the spatial shock is low and disappears in time. Population changes due to forced displacement flows, greater density of young population and low coverage in secondaryeducation affect the diffusion and concentration of homicides in Colombia.